Sleep-Disordered Breathing and Functional Decline in Older Women - Spira, Adam P. (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the association between sleep-disordered breathing (SDB) and decline in instrumental activities of daily living (IADLs) and mobility among older women. DESIGN: Prospective cohort SETTING: Minneapolis and Pittsburgh sites of the Study of Osteoporotic Fractures, participants’ homes PARTICIPANTS: 302 women, mean ±standard deviation age of 82.3 ±3.2 years MEASUREMENTS: Participants completed a single night of unattended polysomnography and provided data regarding difficulty with IADLs and mobility. They repeated IADL and mobility measures 5.0 ±0.7 years later. RESULTS: After adjustment for age, obesity, Mini-Mental State Examination score, depressive symptoms, history of hypertension and chronic obstructive pulmonary disease, and number of IADL impairments at baseline, women with an apnea-hypopnea index (AHI) ≥15 at baseline had more than twice the odds of an increase in number of IADL difficulties (adjusted odds ratio (aOR) = 2.22, 95% confidence interval (CI) 1.09, 4.53) and of incident IADL difficulty (aOR = 2.43, 95% CI 1.0001, 5.92), compared to women with an AHI <5. There was no association between AHI and mobility difficulty. Compared to women in the tertile with lowest oxygen desaturation index, others had more than double the odds of an increase in number of IADL difficulties (middle tertile aOR = 2.64, 95% CI 1.38, 5.04), highest tertile aOR = 2.17, 1.13, 4.17) and approximately three times the odds of incident IADL difficulty (middle tertile aOR = 2.84, 95% CI 1.27, 6.36, highest tertile aOR = 3.07, 95% CI 1.31, 7.18). Neither sleep fragmentation nor sleep duration was associated with IADL outcomes. CONCLUSION: SDB and associated hypoxemia are risk factors for functional decline in older women. Research is needed to determine whether treatment of SDB prevents functional decline.